FAUNA EKHINODERMATA DARI PERAIRAN TANJUNG MERAH SELAT LEMBEH – SULAWESI UTARA - Eddy, Eddy; Susetiono, Susetiono (UI Scholars Hub, 2005)
Notes on the Echinoderm Fauna of the Tanjung Merah Bay Waters Sulawesi Utara. A total of 21 species of echinoderms, belonging to of 5 species holothuroidea, 5 species of asteroidea, 4 species echinoidea and 7 species ophiuroidea have been found in the Tanjung Merah of Sulawesi Utara. The Ophiuroidea were relatively common in the sea grass zone. On the basis of population density, Ophiuroidea was the dominant group and relatively highest in the individual density. The species composition, community structure, zonation, and spatial distribution of echinoderm fauna are discussed in this paper